Performance analysis of DSSS system with periodic sequence against CW interference1 - WEI An-quan1; SHEN Lian-feng 1 (Tongxin xuebao)
Based on the brief account of the performance analysis result of direct sequence spread spectrum（DSSS） system against single tone continuous wave（CW） interference obtained from the traditional stand Gaussian approximation（SGA） hypothesis,the mathematical expression of the interference component of the symbol decision variable in the periodic sequence DSSS system under CW interference was deduced and the actual performance of DSSS system with a periodic sequence against CW interference was researched by theoretical analysis and numerical simulations.The results indicate that the interference component of the symbol decision variable in the periodic sequence DSSS system under CW interference takes on a constant level or a monochromatic fluctuation,which does not approach the standard Gaussian distribution,and the actual performance of DSSS system with a periodic sequence against CW interference is completely different from the analytic result resorted to the stand Gaussian approximation（SGA）.The bit error performance is correlative not only with the interference-signal ratio（ISR）,with the frequency offset and with phase of the CW interference sensitively,but also with the individual spread spectrum code sequence.